Hard-colloidal particles in contact with fluctuating membranes - Córdoba-Valdés, F.; Fleck, C.; Castañeda-Priego, R. (Revista Mexicana de Física, 2007)
A model to study the structural and thermodynamic properties of hard-colloidal particles in contact with fluctuating membranes by means of Monte Carlo simulation is proposed. To test the accuracy of our model, we compare the density profile of a system composed of non-interacting point-like particles with the analytical expression derived by Bickel et al. [Phys. Rev. E 70 (2004) 051404]. This model is applicable to colloids with finite size and it can easily be extended to binary systems or systems with long-range (Coulomb-like) interactions.